Research of Assertiveness in Organization of the Time Perspective of Degree-Seeking Students in Higher Education - Smolinska , Olesia; Koval , Ihor; Pavliuk , Mariia; Shulha , Dmytro (Insight: the psychological dimensions of society, 2024)
The aim is to conduct empirical research and theoretical substantiation of assertiveness of degree-seeking students in higher education within the structure of time perspective. It was substantiated that assertiveness in the organization structure of time perspective is a flexible and constructive strategy and tactic of behavior, reflecting the life position and accompanied by temporal decentrations in the form of dominant representations about the psychological future and psychological past, which is reflected in the current moment of time. Methods. The participants of the research were full-time students of the 2nd and 3rd years of study at higher education institutions in Ukraine, aged from 18 to 20 years (M = 18.44; Me = 18.50; SD = 3.23), with a total number of n = 120 people. A valid and reliable psychodiagnostic toolkit adapted and tested on a Ukrainian sample was applied: “Personality Assertiveness Test” (PAT) (Sheinov, 2014); “Time Perspective Inventory” (TPI) (Zimbardo & Boyd, 1999), adapted by O. Senyk (2012); “Locus of Control” (LC) (Rotter, 1992) and statistical methods for processing empirical data. Theoretical methods were used to perform retrospective analysis, synthesis, and generalization of the main theoretical positions; a discussion was conducted; explanations and justifications of the obtained empirical results and conclusions were presented. Results. Three direct statistically significant correlations were identified between assertiveness and the parameters of “hedonistic present”, “future”, and locus of control. It was found that the correlation between assertiveness and the hedonistic present (rs = .283; p < .001) was the most significant and dependent, and accordingly, the most dangerous. This danger was explained by the fact that material values, which are partly the desire for immediate pleasure, can be understood as the meaning of flexible and constructive behavior of the subjects. A comparison of the studied parameters of the optimal profile (Group 1) with the parameters of the general profile (Group 2) was performed. A statistically significant advantage of the optimal profile in terms of assertiveness and internal locus of control was recorded. Discussion and сonclusions. It was summarized and explained that assertiveness occupies an important place in the structure of time perspective and performs a regulatory role. Educational process organizers were recommended to focus on developing this competence in the students.
Keywords: educational and professional training, students, university, internalization, locus of control, temporal decentration.